Article 10: ENGLISH INSTRUMENTAL - Silva, Me. Só‚nia Mara Braga (2010)
Studying the English language is crucial as it is the commercial language and increasingly required in the professional context. We need the proficiency in that language to have access to new technologies, because it is present in the media that we use in everyday life. The English language is undoubtedly the most important language in the world. It is employed in all kinds of communication among the peoples of our planet. You may have noticed how we Brazilians are familiar with a lot of English words: shopping center, milk shake, hot dog, cheeseburger, bike, surf, etc.